The hygienic assessment of dairy products' selling places at open markets. (June 2023) - Aleksic, Biljana; Djekic, Ilija; Miocinovic, Jelena; Miloradovic, Zorana; Savic – Radovanovic, Radoslava; Zdravkovic, Nemanja; Smigic, Nada
Abstract: Small scale dairy producers, who are often also the sellers of dairy products, are the ones responsible for ensuring food safety conditions all throughout the food distribution chain. Food contamination may appear in any part of the food chain including sale, due to cross-contamination that can occur caused by wide varieties of food offered at open markets, improper food handling, contaminated equipment, and poor personal hygiene. An observational study was conducted to determine the hygienic conditions of artisan dairy products' selling places at open markets. In addition, dairy products' sellers were interviewed to obtain complementary data regarding hygiene conditions at the households, as well as during transportation and sale at the open market. The research included 293 selling places and 279 dairy products' sellers from 43 open markets located in different parts of the Republic of Serbia. Based on a total hygiene assessment score (HAS) calculated for each selling place, acceptable, marginal acceptable and unacceptable group of selling places were identified. A two-step cluster analysis was performed to identify a group of potentially more risky selling places, and resulted in two identified clusters. The differences between hygiene conditions among clusters were mainly influenced by their position at the open market. The establishment and maintenance of a cold chain needs to be improved as one of the most important prerequisites of food safety, especially for those selling places located at an open place. The obtained results suggest the need for additional training and raising awareness of small dairy producers regarding the importance of hygiene during production, distribution and sale of dairy products. Highlights: 55% of dairy products selling places operate at acceptable hygiene. 23.2% of selling places do not have refrigeration units at a point of sale. 75% of dairy products' sellers spend up to 8 h at the open market. The position of selling place has a significant effect on hygienic conditions. Significant hygiene improvements are needed for selling places located outside.